Bilateral Ampiginous Choroiditis following Presumed SARS-CoV-2 Infection. (6th August 2021) - Tom, Elysse S.; McKay, K. Matthew; Saraf, Steven S.
Abstract : Purpose . To report a case of bilateral ampiginous choroiditis following presumed SARS-CoV-2 infection. Case Description . A 25-year-old woman presented with metamorphopsia and a paracentral scotoma in her left eye. She endorsed night sweats, headache, and new-onset anosmia beginning 1 week before her visual symptoms. She also had multiple confirmed ill COVID-19 contacts at her workplace before the onset of her symptoms. Funduscopic examination and multimodal imaging revealed placoid lesions in the macula and midperiphery of both eyes consistent with ampiginous choroiditis. COVID-19 antibody testing returned positive for IgG, and an extensive systemic evaluation was otherwise unremarkable. She was treated with oral prednisone and azathioprine with stabilization of the retinal lesions and no progression of her symptoms. Conclusions . Ampiginous choroiditis is an inflammatory chorioretinopathy with an unknown pathogenic mechanism that often necessitates early immunomodulatory therapy. This report suggests that SARS-CoV-2 infection may trigger chorioretinal inflammation in susceptible hosts.